Aspek Hukum Terhadap Regulasi Wanprestasi Perjanjian Dengan Jaminan Hak Tanggungan - Endang Setyowati (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Cooperation between economic actors such as financial institutions is an embodiment of the concept of the rule of law in economic development. Financial institutions such as banks provide credit to the public but there are also credit risks. So Bank Indonesia issued Guidelines for Preparing Credit Policies (PPKPB) for Commercial Banks, on March 31 1995, through Bank Indonesia Directors' Decree No.27/162/KEP/DIR which contains credit agreements in standard form. The existence of standard clauses in bank credit agreements containing the debtor's obligations, which aim to protect the creditor's interests, is unfair to the debtor. For this reason, it is necessary to study the weaknesses in the regulation of default on agreements with guarantees of mortgage rights. This research is based on John Rawls's Theory of Justice and Lawrence M. Friedman's Legal System Theory. The research specifications are analytical descriptive, with a sociological juridical research type. Regulations on default on agreements with guaranteed mortgage rights have weaknesses in the legal structure aspect, namely the lack of synergy between law enforcement officials. Apart from that, there are weaknesses in the legal substance aspect, namely related to the provisions contained in Article 15 UUHT, as well as weaknesses in the legal culture aspect which can be seen from the public's lack of knowledge about credit agreements and the lack of socialization regarding legal regulations related to the basic principles of agreement law.